DOES GOVERNMENT INTEGRITY ALWAYS IMPROVE FINANCIAL SUSTAINABILITY? THE ROLE OF FINANCIAL FREEDOM IN APEC ECONOMIES - Utami, Rizki Putri; Naimah, Zahroh (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
This study examines whether government integrity consistently improves financial sustainability and explores the role of financial freedom in APEC economies. Financial sustainability is conceptualized as an accounting-based fiscal outcome reflecting governments’ capacity to manage long-term fiscal obligations transparently. Using panel data from 13 APEC member countries during 2010–2024, this study employs a fixed effects panel regression to control for unobserved country-specific heterogeneity. Government integrity and financial freedom are measured using indices from the Heritage Foundation, while financial sustainability is constructed as a composite index derived from key fiscal indicators. The results show that government integrity has a statistically significant but negative association with financial sustainability, suggesting that higher integrity enhances transparency and comprehensive recognition of fiscal obligations, which may initially worsen measured fiscal sustainability due to improved disclosure and accounting recognition effects rather than weaker fiscal discipline. Financial freedom does not exhibit a significant effect, indicating that financial market openness alone is insufficient to ensure sustainable public finances. GDP per capita positively influences financial sustainability.